As Tendências Históricas do Desenvolvimento Brasileiro e suas Relações com o Desenvolvimento Socioespacial Rural na Região Fronteira Noroeste do Rio Grande do Sul - José Tobias Marks Machado (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2018)
The article aims to analyze the development trends experienced in Brazil along the time and to place its ramifications both on agriculture in a wider way, as well as on the evolution of agriculture in the Northwest Frontier region of the state of Rio Grande do Sul. For this, the work was based on the periodization of the three cycles of society and state, proposed by Bresser-Pereira. There is a positive correspondence between the cycles of society and the state and the agriculture dynamics, so that the latest had different and varied functions throughout the three cycles and five pacts experienced in the country. In the current period, although the recognition of heterogeneity of brazilian agriculture, there is no long-term rural development project capable to contemplate all its heterogeneity. As far as agriculture in the northwest frontier region is concerned, this development was associated with the general dynamics of the center. However, the changes that took place during the authoritarian modernizing pact were decisive for the differentiation of regional agriculture, and for the dynamics that still characterize regional agriculture.